Assessing Eastern Europe's Capital Needs - Boote, Anthony (IMF Working Papers; Working Paper, 1992)
The paper aims at assessing the capital needs of Eastern Europe in catching up to EC standards of living using the framework of a CES (constant elasticity of substitution) production function model. This function, parameterized on the EC, is assumed to apply with certain inefficiency factors in Eastern Europe in 1992. Quantitative results, given the heroic set of assumptions required, are bounded by large ranges. The approach provides a framework for assessing the factors which will determine the future capital needs in Eastern Europe and underscores the crucial role of efficiency gains in this process.